Finite-Element Modelling of Double-Roller Clamping Spinning of Wind Concentrator - Qu, Xueyong; Xu, Hongzhong; Fan, Shuqin; Cheng, Xiaole; Zhao, Shengdun; Hua, Yi (Frontiers in Energy Research, 2022)
In order to improve the unit-power of a wind-driven generator, a wind concentrator with complex shape is installed in front of the impeller, which makes the airflow integrated and accelerated. It is important to manufacture the wind concentrator with high precision. The double-roller clamping spinning (DRCS) is a dieless, flexible spinning process that is very suitable for forming a wind concentrator with complex shape. The profile of a wind concentrator is divided into two parts: the contraction section and the expanding section. The process routes of both the contraction section and the expanding section are determined, and roller path equations are derived. Then the finite element (FE) analysis model that can describe the plastic deformation behavior of the DRCS forming for a wind concentrator is established, and the DRCS process of the flange is simulated. Furthermore, the wall-thickness distribution on the expanding section during the forming process is obtained. Finally, the reliability of the FE model is verified using the experimental results.